Experimental Study on Shear Lag Effect of Long-Span Wide Prestressed Concrete Cable-Stayed Bridge Box Girder under Eccentric Load - Yanfeng Li; Jiyuan Xie; Fengchi Wang; Di Wu; Jiahui Wang; Yanao Liu (Construction Materials, 2024)
Based on the engineering background of the wide-width single cable-stayed bridge, the shear lag effects of the cross-section of these bridge box girders under the action of the eccentric load were experimentally studied. The behavior of shear lag effects in the horizontal and longitudinal bridge directions under eccentric load in the operational stage of a single cable-stayed bridge was analyzed by a model testing method and a finite element (FE) analytical method. The results showed that the plane stress calculation under unidirectional live load was similar to the results from spatial FE analysis and structural calculations performed according to the effective flange width described in the design specification. At the position of the main beam near the cable force point of action, the positive stress at its upper wing edge was greatest. At a distance from the cable tension point, the maximum positive stress position trend showed that from the center of the top flange to the junction of the top flange and the middle web to the junction of the top flange and the middle web and the side web. Under eccentric load, the positive and negative shear lag effects on the end fulcrum existed at the same time, and the shear lag coefficient on the web plate was larger than the shear lag coefficient on the unforced side. Due to the influence of constraint at the middle fulcrum near the middle pivot point, positive and negative shear lag effects were significant, and the coefficient variation range was large, resulting in large tensile stress on the roof plate in this area. According to FE analytical results, stress and shear forces of a single box three-chamber box girder under eccentric load were theoretically analyzed, the bending load decomposed into the accumulation of bending moment and axial force, using the bar simulation method, and the overall shear lag effect coefficient λ was obtained and verified.